2020 2nd 6G Wireless Summit (6G SUMMIT) 2020
DOI: 10.1109/6gsummit49458.2020.9083805
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges for Visible Light Communications in 6G

Abstract: This paper discusses the opportunities for visible light communications (VLC) in the future 6G. VLC is a highly attractive optical communication approach for short-range communications, which complements radio. The use of reconfigurable optical-radio networks creates a high performance, highly flexible communication system that can be used in the most stringent environments of 6G. The paper presents and discusses other novel VLC concepts, such as interactive VLC, light-based IoT, living surfaces and optical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 20 publications
0
33
0
2
Order By: Relevance
“…In [103], authors also provided a state-of-the-art of features, strength, and challenges of optical wireless communication for 6G networks. [103,147]  The authors proposed an algorithm for data security in VLC using watermark technique for 6G networks. In [147], several novel concepts such as hybrid-radio optical networks, interactive VLC, optical IoT, and their challenges were discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In [103], authors also provided a state-of-the-art of features, strength, and challenges of optical wireless communication for 6G networks. [103,147]  The authors proposed an algorithm for data security in VLC using watermark technique for 6G networks. In [147], several novel concepts such as hybrid-radio optical networks, interactive VLC, optical IoT, and their challenges were discussed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[103,147]  The authors proposed an algorithm for data security in VLC using watermark technique for 6G networks. In [147], several novel concepts such as hybrid-radio optical networks, interactive VLC, optical IoT, and their challenges were discussed. [36,60,61,118,159] Artificial Intelligence: AI for Edge, and Machine Learning (ML)…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since it is expected that RF frequency resources with a frequency band of up to 300 GHz will be gradually depleted in the future, it is expected that auxiliary services through other transmission media will be needed in order to fully support these IoT services. Among these auxiliary technologies, a light fidelity (Li-Fi) transmission technology, which transmits data wirelessly using light emitted from a white light-emitting diode (LED), is capable of operating IoT services within a special environment such as a hospital and national security facilities [ 10 , 11 ]. In the past 20 years, Li-Fi related research has shown great growth and potential [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The visible and infrared spectrum have been widely considered in wireless communications, either as stand-alone wireless communications technologies or as complementing radio communications. Broadband visible light communication (VLC) has become a highly discussed topic in the fifth generation (5G) as well as in the development of the sixth generation (6G) communication [10]. Wireless infrared communications have been used to transmit data to devices in close vicinity, first standardized by Infrared Data Association (IrDA) [11].…”
Section: Introductionmentioning
confidence: 99%